â€œANALISIS LAPORAN KEUANGAN DENGAN RASIO LIKUIDITAS UNTUK MENILAI KINERJA PERUSAHAAN â€œ(PT HM SAMPOERNA TBK TAHUN 2012-2014)â€ - HELMI HERAWATI herawati (Jurnal Ilmu Akuntansi, 2018)
The purpose of this study is to analyze financial statements with liquidity ratios and to determine the performance of PT. HM Sampoerna Tbk. The nature of this research is descriptive describes something that is studied and then analyzed to provide alternative solutions to the problems studied (Sugiyono: 2007). Analysis of Current Ratio, it is found that the company's ability to guarantee current debt from 2012 is 1.7756 in 2013 at 1.7526 and 2014 is 1.5277 while industry standard for current ratio is 2 times and this result does not meet industry standard. Quick Ratio analysis resulted in 2012 that is 0,4587 year 2013 at number 0,3229 and year 2014 is 0,2460 while industry standard for Quick ratio is 1,5 times and this result do not meet industry standard. Cash Ratio analysis result calculation that cash the company can not guarantee the debt of the company this can be seen from the result of 2012 that is 6,5851 in 2013 at number 5,4213 and year 2014 diangka 0,4785 while industry standard for cash ratio is 50% and this result do not meet industry standard. see the results of ratio analysis above it can be concluded that PT.HM.Sampoerna Tbk is an illiquid company, because the company is unable to guarantee the authority short-term.